URGENSI PERLINDUNGAN HUKUM BAGI PEMBELA HAK ASASI MANUSIA (HUMAN RIGHTS DEFENDER) DI INDONESIA - Rahayu Rahayu (Masalah-Masalah Hukum, 2010)
Human rights defenders are they working and having activities dealing with any effort to promote human rights. They stand in the front tine of struggle and dignifying human rights to utter the victims of human rights violation (the voice of the voiceless). Their existence is obviously recognized in United Nations' Genera! Assembly Nr. 53/144 on "Declaration on the Right and Responsibility of Individuals, Groups and Organ of Society to Promote and Protect Universally Recognized Human Rights and Fundamental Freedom" that was legalized on December 9, 1996. This declaration reaffirms the advocates' rights that is factually protected by UDHR (article 19 and 20), ICCPR (article 21 and 22), ICESCR (article 8), CERD (article 5 d viii and ix) and some other UN's resolution on human rights. Indonesia is a country having problems with human rights defenders. Their existence is legally recognized by article 28 C (2) of the Indonesian Constitution (UUDNR11945) but there is no a single regulation thai specifically states about protection to them in conducting their activities. This fact makes human rights violation against them easily and frequently happen. This is also a proof picturing that the State's duty to protect, promote, erect, and prevail human rights as stated in article 281 (4) ofUUDNR11945 has not been welt accomplished. As part of international society, Indonesia would not be able to escape from the present global trend, that is to put human rights matter as one of the central issues in international relations